1997
DOI: 10.1177/000348949710600802
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Heritability of Recurrent Ear Infections

Abstract: The distribution of recurrent ear infections was obtained from a population-based sample of 2,750 pairs of Norwegian twins born between 1967 and 1974. The lifetime prevalence of self-reported recurrent ear infections was 8.9%, with a significant predominance of female cases. The mean age of onset was 4.2 years, with a gradual decrease in occurrence from 2 to 7 years of age. Among monozygotic pairs, the rate of tetrachoric correlation between co-twins was almost identical in males (0.73, SE 0.08) and females (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 16 publications
5
63
1
4
Order By: Relevance
“…13,30,31 Girls were overrepresented in the group of children who suffered from Ն4 AOM episodes when compared with the children who had 2 to 3 AOM episodes. Children under the age of 4 were more likely to have had Ն4 AOM episodes in the previous year than older children.…”
Section: Tnfa Promoter Genotypes ؊238 G/g and ؊376 G/g And Tlr4 299 Dmentioning
confidence: 89%
See 1 more Smart Citation
“…13,30,31 Girls were overrepresented in the group of children who suffered from Ն4 AOM episodes when compared with the children who had 2 to 3 AOM episodes. Children under the age of 4 were more likely to have had Ն4 AOM episodes in the previous year than older children.…”
Section: Tnfa Promoter Genotypes ؊238 G/g and ؊376 G/g And Tlr4 299 Dmentioning
confidence: 89%
“…9 The influence of genetically determined variations on otitis media can be illustrated by twin studies, which have shown a heritability of 57% for acute ear infections and 72% for chronic ear infections. [10][11][12][13][14] Correlation for recurrent otitis media is higher in monozygotic twins (65%-71%) compared with dizygotic twins (25%-34%). 15 Streptococcus pneumoniae is an important pathogen in otitis media and is involved in at least 20% to 40% of all cases.…”
mentioning
confidence: 99%
“…The first family study of COME/ROM (Daly et al 1996) demonstrated that first-degree relatives (parents and siblings) of probands with COME/ROM had greater than expected rates of OM based on population rates. Subsequent twin and triplet studies confirmed the strong familial aggregation of COME and ROM, with heritability estimates of 0.64-0.74 in monozygotic twins and 0.20-0.53 in dizygotic twins (Kvaerner et al 1997;Casselbrant et al 1999;Rovers et al 2002;Kvestad et al 2004Kvestad et al , 2006. Two linkage studies for COME/ROM have been published to date (Daly et al 2004;Casselbrant et al 2009;Chen et al 2011); however, the loci identified in the two studies did not overlap.…”
Section: Introductionmentioning
confidence: 94%
“…These factors probably function in a complicated interplay. In 2,750 pairs of Norwegian adult monozygotic and heterozygotic twins Kvaerner et al (1997a) estimated that the variation in liability for recurrent ear infections consisted of 74% heritability in females and 45% in males. URTI's have been claimed to be the most powerful risk factor associated with OM (Maynard 1969, Fleming et al 1987, Harsten et al 1989, Arola et al 1990, Alho et al 1990, Aniansson et al 1994, Daly et al 1999.…”
Section: Aimsmentioning
confidence: 99%